AWARENESS OF THE EFFECTS OF SOCIAL MEDIA AMONG ELDERLY POPULATION - Kamalli. M; Priya, V. Vishnu; R. Gayathri (International Journal of Psychosocial Rehabilitation, 2020)
A social media is an internet platform which individuals use to create social networks or social relations with others who share similar personal interests and career interests or real life connections. The social media allows the elderly to face more easily the difficulties of modern life, trespassing the limits of their social and emotional isolation.The aim of the study is to determine the awareness on the effects of social media among elderly population. Self-administered questionnaire was designed and distributed through an online survey planet link based on the effects of social media.Study population included the elderly population belonging to age group between 50-60 years. Data was collected and statistically analysed. It was observed that elders were aware of the effects of social media. 83% of elders agreed social media affected mental health.71% of them agreed that sleep was affected by usage of social media. 67% of participants thought there are more positive effects than negative effects. 46% of elders felt that mental health was majorly affected by means of thought process.81% of participants feel that social media is influential on academics.65% of them feel social media is a boon and 35% of the elders social media is a bane. The study may conclude that elders were aware of the effects of social media and felt that social media improved their knowledge on global scenario.